2021
DOI: 10.1109/access.2021.3075573
|View full text |Cite
|
Sign up to set email alerts
|

Fake Reviews Detection: A Survey

Abstract: In e-commerce, user reviews can play a significant role in determining the revenue of an organisation.Online users rely on reviews before making decisions about any product and service. As such, the credibility of online reviews is crucial for businesses and can directly affect companies' reputation and profitability. That is why some businesses are paying spammers to post fake reviews. These fake reviews exploit consumer purchasing decisions. Consequently, the techniques for detecting fake reviews have extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(29 citation statements)
references
References 137 publications
(187 reference statements)
0
29
0
Order By: Relevance
“…Machine Learning comes with many classification algorithms. In a recent study [21], they came up with a survey report and concluded that machine learning algorithms perform well on medium-sized datasets as compared to Artificial Neural Network (ANN) and deep learning models, which are a good fit for large size datasets. Feature engineering is another reason ANN and deep learning models do not show better results for fake review detection.…”
Section: B Classification Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Machine Learning comes with many classification algorithms. In a recent study [21], they came up with a survey report and concluded that machine learning algorithms perform well on medium-sized datasets as compared to Artificial Neural Network (ANN) and deep learning models, which are a good fit for large size datasets. Feature engineering is another reason ANN and deep learning models do not show better results for fake review detection.…”
Section: B Classification Algorithmsmentioning
confidence: 99%
“…Moreover, fake review detection is more challenging with realistic datasets with overlapping between legitimate and fake review data. [21].…”
Section: Experimentation Design / Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from detecting such reviews, identifying spamming individuals and their possible associations have also been pursued. Machine learning and graph-based approaches have been explored too [4]- [6]. A major problem in this field is the lack of a standard dataset.…”
Section: Introductionmentioning
confidence: 99%